2009
DOI: 10.2341/08-74
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Effectiveness of Various Tooth Whitening Systems

Abstract: ©Operative Dentistry, 2009, 34-2, 230-235 BA Matis • MA Cochran • G Eckert Clinical RelevanceTooth whitening is observable with all methods of bleaching. Dentist-prescribed overnight bleaching was shown to be the most effective method of bleaching. SUMMARYThis review compares nine published studies conducted at the Indiana University School of Dentistry. Twenty-five products in four different systems were evaluated using the Trubyte Bioform Color Ordered Shade Guide and a Chroma Meter. The dentist-prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 10 publications
1
89
0
6
Order By: Relevance
“…The degree of whitening obtained in this study is similar to that reported in other clinical trials 9,17,19 and also in the literature review. 1 Finally, it should be mentioned that only a value-oriented shade g uide was used for identification of color changes throughout the study period. This was done because it is an easy, fast, and satisfactory method used in several investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of whitening obtained in this study is similar to that reported in other clinical trials 9,17,19 and also in the literature review. 1 Finally, it should be mentioned that only a value-oriented shade g uide was used for identification of color changes throughout the study period. This was done because it is an easy, fast, and satisfactory method used in several investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, this bleaching protocol has a very high risk of tooth sensitivity, which may occasionally be severe. 1,2 Bleaching-induced tooth sensitivity has been associated with microscopic surface defects and sub-surface pores in the enamel, 3 with consequent reduction in enamel microhardness. 4,5 This is because of the low pH of the in-office bleaching gels available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…This last change color was mainly related to increasing on lightness and reduction on yellowness, whereas the no significant modification on redness was observed. The measurement of color after 30 days was chosen to determine any residual effect of tooth bleaching and to simulate clinical conditions when a rebound effect has been demonstrated (3,24). The rebound effect tends to slight reduce the effect reached by tooth bleaching and is mainly due to physiological response to pulpal damage.…”
Section: Discussionmentioning
confidence: 99%
“…The tooth bleaching techniques performed either in office or by patients at home are carried out using bleaching agents based on hydrogen or carbamide peroxides (3)(4)(5). The bleaching effect is achieved due to oxidative action of peroxides and its sub-products on the organic matrix of the tooth tissues modifying its optical properties (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, simpler molecules that diffuse out of the tooth or reflect less light are formed, creating a successful bleaching action. 2 The bleaching reaction depends upon the type of discoloration involved and the chemical and physical environment present at the time of action, that is, concentrations, 2,3 heating, 4 lightening, 5 pH, 6 co-catalysts, [7][8][9][10] times of application, 3 and other conditions. Most current office bleaching products employ high concentration H 2 O 2 to produce higher amounts of free radicals.…”
Section: Introductionmentioning
confidence: 99%